Kinerja Usaha Namar Farm Hidroponik Menggunakan Balanced Scorecard di Kabupaten Rejang Lebong Bengkulu - Pratama, Dicky Rolanda; Mulyasari, Gita; Reswita, Reswita; Cahyadinata, Indra; Windirah, Nola (MuJAgri: Musamus Journal of Agribusiness, 2024)
Namar Farm Hydroponics is a business that cultivates vegetables using a hydroponic system, so the impact on investment and production costs is more significant than that of the conventional vegetable cultivation process. This research aims to analyze the performance of the Namar Farm Hydroponic vegetable business in Rejang Lebong Regency, which includes financial aspects (financial perspective) and non-financial aspects (perspective, customers, internal business process perspective, and growth and learning perspective). The research location was determined deliberately or purposively, and the analysis used was a balanced scorecard (BSC). The results showed that (1) the financial aspect, from a financial perspective, scored 50% in the sufficient category. The average profit per month received by the Namar Farm Hydroponics business is Rp. 6,373,800.75. The R/C Ratio value is 1.68, while the BEP value in Rupiah is Rp. 3,740,649.13. (2) In the non-financial aspect, it is categorized as sufficient with a score of 50%. The following is the score for each perspective. From the customer perspective, it is known that the Namar Farm Hydroponic customer satisfaction score is 76.2 (satisfied). From the internal business process perspective, it is 82.66% with the category "good." From the learning and growth perspective, employees' satisfaction with the Namar Farm Hydroponics business is 80%, and they are "satisfied." In comparison, the retention of workers is 50% (less), so the performance from the learning and growth perspective is categorized as "adequate." (3) The results of the overall performance measurement using the Balanced Scorecard (BSC) method in the Namar Farm Hydroponics business obtained a score of 50% with the "enough" category.